The Influence of Christianity upon the Roman Empire - McGiffert, Arthur Cushman (Harvard theological review, 1909)
It has commonly been taken for granted that Christianity must have had a great and beneficent influence upon the Roman Empire, within which it had its origin and whose official religion it finally became. This not unnatural assumption is, however, very difficult to substantiate. One may recognize that the religion of Christ was a great advance upon the paganism of antiquity, and that its final victory was a blessing to the world, and yet find it far from easy to show how and to what extent the Roman world was benefited by it. It is simple enough to point to individual lives within the Christian church that were purified and helped. But to prove that the common level of life within the Empire was raised, that society at large was bettered, that the general moral standard was elevated, that political principles and civil institutions and economic ideals were improved by its influence, is altogether another matter. It is not enough to content ourselves with the assumption that Christianity being in itself a good thing must have been good for the Roman world; it is incumbent upon us to show that it actually proved so.